Studies on the Effect of Mono-Alkoxy Pyrophophato Coupling Agent on the Mechanical Properties of Magnesium Hydroxide Filled HDPE/EVA/Mg(OH)2/Composites - Alkadasi, Nabil A. N. (Thamar University Journal of Natural & Applied Sciences, 2023)
Effect of treatment of coupling agent (mono-alkoxy pyrophophato coupling agent) on mechanical properties of composites made from HDPE/EVA/Mg(OH)2/ Composites is reported here. The coupling agent in the form of solution (1.5%) was used for treatment of the filler .The treatment resulted in enhancement of mechanical properties of composites when compared with composites containing untreated Magnesium hydroxide. The properties under consideration were tensile strength, modulus at (%) elongation at break, elastic modulus, hardness, etc. Although good reinforcement was observed due to treatment of 1.5% coupling agent, observed was very much remarkable by its comparing to untreated once. Comparison of properties of composites filled with treated and untreated Magnesium hydroxide established that the treatment of Magnesium hydroxide imparts better reinforcing properties. The properties under consideration were tensile strength, (%) elongation at break, elastic modulus, hardness, etc. Tensile strength was improved by 19.10%, (%) elongation at break was improved by 9.01%, elastic modulus was improved by 100%, while hardness was improved by 0.5%, at (0.14) volume fraction.